MODELLING AND SIMULATION OF DYNAMIC VIBRATION ANALYSIS OF ROTOR-BEARING SYSTEMS UNDER UNBALANCE AND HARMONIC EXCITATIONS - Ofuyekpone, Okiemute Dickson; Utu, Ochuko Goodluck; Eduviere, Oghenemaro Geraldine; Naenwi, Yaabari (FUDMA Journal of Sciences, 2026)
Rotor–bearing systems in rotating machinery frequently experience vibration due to mass unbalance, particularly at elevated operating speeds. While advanced multi-degree-of-freedom rotor models exist, many studies focus primarily on detailed numerical simulations without providing simplified parametric tools that assist engineers in interpreting vibration trends during preliminary design stages. This lack of transparent parametric insight represents an important gap in practical rotor dynamic analysis. This study investigates the vibration behavior of a rotor–bearing system subjected to unbalance-induced harmonic excitation using a single-degree-of-freedom (SDOF) linear dynamic model. The SDOF formulation was intentionally adopted to enable clear parametric interpretation of system behavior while preserving the essential physics of rotor vibration. To provide generalized interpretation, resonance behavior was analyzed using dimensionless parameters, including the normalized frequency ratio and damping ratio. The results demonstrate that vibration amplitude increases significantly as the normalized speed approaches unity, corresponding to the resonance region, while higher damping ratios effectively suppress vibration amplitude. Such that, at an operating speed of 388 rad/s, increasing the damping coefficient from 50 Ns/m to 100 Ns/m reduces the peak displacement from approximately 0.010 m to 0.005 m. A vital contribution of this work was the development of a speed–damping response surface, which maps peak rotor displacement as a function of operating speed and bearing damping. The proposed modeling and visualization framework offers a simple yet effective approach for preliminary rotor dynamic assessment and can support improved design and maintenance planning for rotating machinery.
Keywords: Rotor–bearing system; Unbalance excitation; Vibration analysis; Harmonic excitation